Implementasi Program Keluarga Harapan (PKH) di Desa Ngesti Rahayu - Ari Gusnita; Daud Husni; Joko Mulyono (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Kendari, 2022)
The Family Hope Program Assistance (PKH) in its implementation is still not in harmony with the government's goals. Inequality, injustice and mistargeting are highlighted in this study. This type of research is descriptive qualitative and data collection techniques are carried out through observation, interviews and documentation. The results show that the implementation of this program has not been effective because the program targets in the field are not appropriate and the people who receive it are not evenly distributed.